Analisis Efektifitas Safari Layanan Informasi UKWMS dengan Menggunakan Consumer Decision Model - Utami, Chr. Whidya; Susilawati, C. Erna (Jurnal Widya Manajemen & Akuntansi, 2003)
Widya Mandala Surabaya Catholic University (WMSCU) as an educational institution considering needs to do a promotion activity. The university chooses personal selling by forming team called Safari Information Services as a promotion tool. By using Consumer Decision Models (CDM), this study try to examine the effect of the Safari Information Services Message toward students buying intention to the Economic Faculty of WMSCU through institution name introduction, students trust and students attitude. The result of this study shows that CDM isn't effective as a model in the process of students making decision to enter Economic Faculty of WMSCU. Inspite of that Safari Information Services messages have the effect toward students buying intention through the institution name introduction, students trust and student attitude.